Personality profile of Spanish basketball referees: Differences between elite and non-elite performers - Goma-i-Freixanet, M.; Pla-Cortes, J.; Aviles-Anton, O. (Personality and Individual Differences, 2014)
Sports Psychology has not paid much attention to the referee, despite the importance of his decisions in the court. Several studies have shown that their personality profile differs from the general population and that there also exist differences according to the level of excellence they have achieved. The NEO PI-R was administered to 402 Spanish male basketball referees. A differential personality profile was found between the referees and the general population, as well as between two groups of referees differing on the level of excellence. Referees scored higher than general population on Neuroticism and lower on Openness, Agreeableness and Conscientiousness. The facets of Competence and Assertiveness distinguished between referees according to the level of excellence they had achieved. The results of this study encourage the implementation of training plans aimed at ensuring referees exhibiting desirable personality traits which are currently not found in their usual repertoire of competences.